Geração distribuida utilizando micro-centrais hidro-elétricas com tecnologia assíncrona - Rondina, José Mateus (2007)
This work approaches the induction machine s technical viability on small hydropower plant instead of synchronous machines, as a viable economically alternative of generating electric energy, matching conventional and decentralized generation visualizing micro generation. This technology makes it possible to skirt a series of problems in the conventional model, as well as lowering tax of ambient impacts. According to the level of consumption, it could generate income for small proprietors, which results the possibility of great impacts on social order. This work presents a distributed generations evolution s synthesis. It also contemplates information about alternative sources of energy, distributed generation s impacts at compositing the energy matrix, as well as it s perspective. In addition to that, it focuses on the main advantages and disadvantages of the distributed generation, emphasizing the conventional electric energy generation model by means of small hydropower plant generation using synchronous and the model using induction machines which is proposed on the presented work. It also presents the development of an archetype, as well as the carried through experimental laboratory and field. At least, the work boards, through digital simulations, a study of agricultural distribution system s results of the prototype area, using the local net real data and simulating the injection of the gotten power of the prototype.